Архівознавство у науковій спадщині Володимира Іконникова - Войцехівська, І. (Архіви України, 2008)
The article deals with the some issues of archival studies, in particular, the issue of history of archival affairs as the subject of the fundamental “Experience of Russian Historiography” written by V. Ikonnykov, a prominent Ukrainian historian. On the basis of this work the author conducts the analysis of the documents of numerous Russian archives, such as central, state, hubernskyie (provincial), municipal, monastery, private and personal.